2010
DOI: 10.1590/s1808-86942010000200004
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da audição em crianças com fissura labiopalatina não-sindrômica

Abstract: Chi ldren with cleft lip/palate often present otitis media as a result of anatomic and/or functional alterations of the Eustachian tube. Aim: to analyze the results of Basic Audiologic Evaluation (BAE) and Auditory Processing Screening (APS) in children with cleft lip/palate. Study design: prospective cross-sectional cohort. Materials and methods: Forty-four male and female children, within the 8 to 14 age range with non-syndromic cleft lip/palate, referred by the institution where the study was carried out. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 15 publications
2
20
0
13
Order By: Relevance
“…the correct spelling of some words based on the sound; and on the stage prior to literacy, to express the thoughts by continuous interaction of speech and writing 11 . The incidence of related deficits on cognitivelinguistic skills, predictors for learning how to read and write, observed in G1, was consistent with other findings, including children with cleft lip and palate in their literacy phase 6,10,19 . However, as both groups showed impairments concerning pre-skills for learning how to read and write, this finding may represent the skill in its development process, instead of being consolidated.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…the correct spelling of some words based on the sound; and on the stage prior to literacy, to express the thoughts by continuous interaction of speech and writing 11 . The incidence of related deficits on cognitivelinguistic skills, predictors for learning how to read and write, observed in G1, was consistent with other findings, including children with cleft lip and palate in their literacy phase 6,10,19 . However, as both groups showed impairments concerning pre-skills for learning how to read and write, this finding may represent the skill in its development process, instead of being consolidated.…”
Section: Resultssupporting
confidence: 89%
“…The children with cleft lip and palate may present speech 7 , orthodontic 8 and emotional 3 , disabilities, and therefore these conditions are considered as risk factors for low academic performance 9 . Although some studies report no relationship between facial deformity and intellectual underperformance 10 , others report deficits in cognitive abilities of children with cleft lip and palate, justified by alterations in auditory functions and / or speech, essential to the learning process, including reading.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 50 patients having cleft palate were included whereas isolated cleft lip patients were excluded from the study, as it has been found that the incidence of hearing problems in cleft lip alone is the same as in the controlled population, which however increases sharply when there is associated submucous cleft palate in this group [15]. Previously published studies were devoid of uniformity in age group of study subjects and age stratified data.…”
Section: Discussionmentioning
confidence: 99%
“…The risks for language change, the changes are given in the middle ear, such as frequent episodes of otitis media with sensory deprivation, which can lead to phonological errors [9]. As for the different aspects of language in the early stages of language development, problems of resonance and articulation can cause phonetic and phonological changes and thus significantly interfere with the quality of speech.…”
Section: Introductionmentioning
confidence: 99%